A New Approach to Optimizing the Treatment and Prevention of Atopic Cheilitis against the Background of Allergic Diseases in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Atopic isolated cheilitis is mainly combined with the most significant changes in immunocompetent cells and, first of all, those characterizing the T-cell link.In atopic forms of cheilitis, all classes of immunoglobulins are involved in detoxification mechanisms, as evidenced by positive correlations with indicators of endogenous intoxication. In addition, tension in the elimination function of the kidneys and salivary glands was noted.